Modifikasi Desain Konstruksi Alat Bending V Dengan Sistem Hidro Pneumatik - Rusdi Nur; Muhammad Arsyad Suyuti; Arial Arial; Farid Hidayat Arfa; Andi Fadel Ahmad (Politeknik Negeri Ujung Pandang, 2023)
Many forms of technological development aim to answer the need for human work efficiency, so an effective technology development effort is very necessary. As the times progress, of course, there are many changes, especially in science and technology, which may have shifted completely in the industrial area, meaning that in this change it is necessary to require extra operations, namely human labor replaced by machine power. One of them is a plate bending machine or what is called a bending machine. The purpose of this program according to the formulation of the problem above is to maximize the drive system and bending system so that the bent plates form a 90Â° angle. This research includes several things such as sketching or drawing of bending tools to be modified, as for what we modified, namely the replacement of the top and a larger bottom plate so that the pressing system functions properly, as well as the replacement on the spring so that it matches the load received by the spring. After determining the form of the construction design of the plate bending tool, then determine the concept of each main component of the plate bending tool in order to get maximum and good bending results. The data from the test results of this portable bending tool were tested with different plate thicknesses, namely 2 mm, 3 mm and 4 mm plates. Tests were performed on each thickness using the maximum bending line. Based on the tests carried out using this bending tool that the drive system works optimally and the bending system works properly and the maximum bending on a plate with a thickness of 4mm can be bending at the right angle of 90Â° is said to work optimally.